Double-coated enrofloxacin microparticles with chitosan and alginate: Preparation, characterization and taste-masking effect study. (15th August 2017) - Liu, Mengxi; Yin, Daiping; Fu, Hualin; Deng, Fengying; Peng, Guangneng; Shu, Gang; Yuan, Zhixiang; Shi, Fei; Lin, Juchun; Zhao, Ling; Yin, Lizi; Fan, Guoqing
Graphical abstract: Highlights: Double-coated taste-masking enrofloxacin microparticles (DTME) were developed and characterized. The measured bitter taste detection threshold value of ENRO is 2 mg/mL for pigs. It was proved that DTME have good cover effect to the bitter taste of enrofoxacin. Abstract: Enrofloxacin (ENRO) is widely used as an antimicrobial drug for treatment of uncomplicated and complicated infections in veterinary medicine. Its bitter taste limits its clinical applications in veterinary. To mask the bitter taste of this drug, double-coated taste-masking microparticles of ENRO (DTME) were prepared through stearic acid solid dispersion and chitosan-alginate microparticle coating technologies. The taste-masking effect was evaluated by pig feeding experiment. Results showed that DTME exhibited a spherical-like shape (170490 μm). DTME yielded a drug loading rate of DTME 20.3% and an entrapment efficiency of 89.8%. The bitter detection threshold value of ENRO for pigs is 2 μg/mL. The drug release amounts of DTME within 30 s were less than 2 μg/mL in artificial saliva. Compared with normal food intake, the food intake of pigs decreased 28.65% when fed with fodder containing free ENRO and slightly increased (0.18%) when fed with fodder containing DTME. Therefore, DTME masked the bitterness of ENRO and improved its palatability. In conclusion, DTME showed satisfactory bitter taste-masking property; this novel formulation was likely to provide more selectable dosage forms for ENRO.